2020
DOI: 10.23887/jpbi.v8i2.28663
|View full text |Cite
|
Sign up to set email alerts
|

Strategies in Teaching Reading to Visually Impaired Students

Abstract: This study aimed to determine the strategies that are used in teaching reading to visually impaired students and the challenges in teaching reading to visually impaired students in SLB Negeri 1 Tabanan.  The research design used was a descriptive qualitative design. Subject of the study was the students with visually impaired in SLB Negeri 1 Tabanan which amounted 5 students. Data were collected by video recording, field note, and interview. Then, data were analyzed qualitatively. The results showed that (1) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…These learning principles can be implemented in a good learning environment for blind students (Setiawan et al, 2020). According to Sunanto (2015), These learning principles can be carried out with the support of a good learning environment for blind students.…”
Section: Benefits For Students With Visual Impairmentmentioning
confidence: 99%
“…These learning principles can be implemented in a good learning environment for blind students (Setiawan et al, 2020). According to Sunanto (2015), These learning principles can be carried out with the support of a good learning environment for blind students.…”
Section: Benefits For Students With Visual Impairmentmentioning
confidence: 99%
“…Idioms are considered to be a type of figurative language that contains confusing linguistic features that language learners are exposed to while learning the language, idioms are not literally translated. According Seran (2020) idioms are a part of socio-cultural aspects and necessitate those language users employ the target language's grammar and vocabulary. According to Shakouri and Nafissi (2019) idioms have their own, distinct meaning from figurative meaning.…”
Section: Introductonmentioning
confidence: 99%
“…Moreover, using assistive technology in English learning for visually impaired students has been demonstrated to be beneficial in several previous studies. Setiawan et al (2020) found that the teacher used e-text concerning the JAWS application and an auditory technique (Live Reader with a story called My School and Live Reader with multiple-choice tests) to assist visually impaired students in reading English. Fansury et al (2019) revealed that implementing audiobooks as teaching media for blind students in learning English could help students in the learning process.…”
Section: Introductionmentioning
confidence: 99%